African heritage in a changing climate. Issue 3 (2nd July 2020) - Brooks, Nick; Clarke, Joanne; Ngaruiya, Grace Wambui; Wangui, Elizabeth Edna
ABSTRACT: Climate change is a real and present threat to heritage across the world. In Europe and North America, research on the impacts of climate change on heritage, including how to mitigate against more frequent extreme weather events and how to implement efficient sustainable adaptation planning, are now key foci of heritage literature. In contrast, virtually nothing has been written about the impacts of climate change on heritage on the African continent, even though these will be significant in the coming decades. Heritage is essential for livelihoods, but also for the construction and reinforcement of identity and the psychological wellbeing of society. Here, we consider the impacts of climate change on different (connected) forms of heritage in Africa, including archaeological, historical and living heritage. We situate the implications of climate change for African heritage in recent debates around climate justice, sustainability and social wellbeing. We conclude that without significant intervention some of Africa's most important heritage will be lost as a result of the direct and indirect impacts of climate change over the coming decades. Our intention is to draw attention to the need for research into the impacts of climate change on different forms of heritage in Africa and to highlight the possible deleterious effects these losses will have on society more generally. We view this paper as a first step in developing a research agenda that will have a practical application for the management of heritage in the face of climate change in Africa.